New-generation drug eluting stent vs. bare metal stent in saphenous vein graft – 1 year outcomes by a propensity score ascertainment (SVG Baltic Registry). (1st October 2019) - Wańha, Wojciech; Mielczarek, Maksymilian; Roleder, Tomasz; Ładziński, Szymon; Milewski, Marek; Gilis-Malinowska, Natasza; Chmielecki, Michał; Ciećwierz, Dariusz; Bachorski, Witold; Kunik, Piotr; Trznadel, Agata; Męcka, Klaudia; et al.
Abstract: Background: Data regarding the efficacy of the percutaneous coronary intervention (PCI) with new-designed drug-eluting stent (new-DES) vs. bare metal stent (BMS) of saphenous vein grafts (SVG) stenosis is scarce. The primary objective was to compare one-year clinical outcomes of PCI in stenosis of SVG using new-DES vs. BMS in a real-world population. Methods and results: We carried out a multi-center registry comparing new-DES with BMS in all consecutive patients undergoing PCI of SVG. The primary composite endpoint was major adverse cardiac and cerebrovascular events (MACCE) at 1 year. This observation included 792 consecutive patients (mean age 69 ± 8.9y), treated with either new-DES ( n = 379, 47.9%) or BMS ( n = 413, 52.1%). Among patients treated with new-DES compared with BMS, there was a lower risk of MACCE (21.4% vs. 28.3%, HR = 0.69, 95% CI 0.50–0.95, p = 0.025) as well as myocardial infarction (MI) (6.3% vs. 12.1%; HR 0.49, 95% CI 0.30–0.82, p = 0.005) at 1 year. After propensity score adjustment, the similar, significant reduction in MACCE and MI was observed in favor of new-DES (HR 0.66, 95% CI 0.46–0.96, p = 0.030; and HR 0.53, 95% CI 0.31–0.92, p = 0.020, respectively). Conclusion: In patients undergoing PCI of SVG, the use of new-DES is associated with a reduced 1-year rate of MACCE and MI compared to BMS. Highlights: New-DES vs. BMS in PCI of SVG is subject to discuss. SVG PCI using new-DES showed favorable clinical outcomes in terms of 1-year rate of MACCE and MI compared to BMS. SVG Baltic Registry support new-DES as the mainstay stent technology in patients undergoing PCI of SVG.